2015
DOI: 10.5961/jhes.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of women academicians' perceptions regarding “being a woman academician” through metaphors

Abstract: Bu çalışmanın amacı kadın akademisyenlerin "kadın akademisyen" olmaya yönelik algılarını metaforlar yoluyla analiz etmektir. Araştırmanın çalışma grubunu 2013-2014 akademik yılında İç Anadolu Bölgesi'ndeki yeni kurulan bir üniversitede çalışan 67 kadın öğretim elemanı oluşturmaktadır. Verilerin toplanmasında araştırmacılar tarafından geliştirilen "Kadın Akademisyen Metaforları Anketi" kullanılmıştır. Olgu bilim deseninin kullanıldığı araştırmada veriler içerik analizi tekniği kullanılarak çözümlenmiştir. Veril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the study, it was determined that female mathematics teachers formed 71 different metaphors concerning the concept of "FM", which shows that the concept of "FM" cannot be explained with only one metaphor. Similarly, Sozer and Ozkan (2014) determined that pre-service social studies teachers explained the phenomenon of "woman" with 49 different metaphors, Basarir and Sari (2015) determined that female academicians explained the concept of "being a female academician" with 65 different metaphors and Ozkan (2017) determined that students at faculties of education explained the concept of "woman" with 234 different metaphors. In addition, the metaphors specified by the teachers also reveal their awareness about FMs.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study, it was determined that female mathematics teachers formed 71 different metaphors concerning the concept of "FM", which shows that the concept of "FM" cannot be explained with only one metaphor. Similarly, Sozer and Ozkan (2014) determined that pre-service social studies teachers explained the phenomenon of "woman" with 49 different metaphors, Basarir and Sari (2015) determined that female academicians explained the concept of "being a female academician" with 65 different metaphors and Ozkan (2017) determined that students at faculties of education explained the concept of "woman" with 234 different metaphors. In addition, the metaphors specified by the teachers also reveal their awareness about FMs.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Similarly, Sozer and Ozkan (2014) and Ozkan (2017) grouped the metaphors of pre-service teachers concerning the phenomenon of "woman" under six categories. Basarir and Sari (2015), on the other hand, explained the metaphors of female academicians concerning the concept of "being a female academician" under nine categories. While the categories examined, it was concluded that teachers generally had a positive viewpoint of the concept of "FM".…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perception is the mental pictures created which influence our construction of reality. In their study (Mediha & Fatima, 2015) concluded that participants ascribe to attributes such as motherhood, sacrifice, fragility as feminine to female teachers whilst the features such as authority, power, leadership, discipline are accepted as masculine to male teachers. In their conclusion they considered their finding as an indicator that male teachers are not sufficiently aware of the multiple roles and responsibilities that their female counterparts have; maybe even describe them as 'inefficient and problematic workers' and 'elegant and fragile existences' (pp220).…”
Section: Perception Of Male Teachers About Female Mathematics Teachersmentioning
confidence: 99%